SSEP in Therapeutic Hypothermia Era. Issue 5 (September 2017) - Maciel, Carolina B.; Morawo, Adeolu O.; Tsao, Ching Y.; Youn, Teddy S.; Labar, Douglas R.; Rubens, Elayna O.; Greer, David M.
Abstract : Purpose: The reliability of somatosensory evoked potentials (SSEPs) in predicting outcome in comatose survivors of cardiac arrest treated with therapeutic hypothermia (TH) has been questioned. We investigated whether the absence of cortical (N20) responses was a reliable predictor of a nonawakening in the setting of TH. Methods: A retrospective review was conducted in cardiac arrest survivors treated with TH admitted to a single tertiary care hospital from April, 2010 to March, 2013 who underwent SSEP testing at various time points after cardiac arrest. N20 responses were categorized as normal, present but abnormal, bilaterally absent, or inadequate for interpretation. Neurologic outcome was assessed at discharge by the Cerebral Performance Category Scale (CPC). Results: Ninety-three SSEP studies were performed in 73 patients. Fourteen patients had absent N20 responses; all had poor outcome (CPC 4–5). Eleven patients had absent N20 s during hypothermia, three of whom had follow-up SSEPs after rewarming and cortical responses remained absent. Fifty-seven patients had N20 peaks identified and had variable outcomes. Evaluation of 1 or more N20 peaks was limited or inadequate in 11.4% of SSEPs performed during the cooling because of artifact. Conclusions: Somatosensory evoked potentials remain a reliable prognostic indicator in patients undergoing TH. The limited sample size of patients who had SSEP performed during TH and repeated after normothermia added to the effect of self-fulfilling prophecy limit the interpretation of the reliability of this testing when performed during cooling. Further prospective, multicenter, large scale studies correlating cortical responses in SSEPs during and after TH are warranted. Technical challenges are commonplace during TH and caution is advised in the interpretation of suboptimal recordings.